Synthesis and antioxidant activity of two isoespintanol (2010)
The antioxidant activity of isoespintanol (1) hemisynthetic analogues, 4-bromo-2- isopropyl-3,6-dimethoxy-5-methylphenol (2) and 3-isopropyl-6-methylbenzene- 1,2,4-triol (3), was evaluated using ABTS, DPPH and FRAP assays. Partial rationalization of the results is provided in terms of quantum chemical calculations of bond dissociation enthalpy (BDE) and ionization potential (IP).